1997
DOI: 10.1023/a:1007919921991
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: Temperature reduction in CHO cell batch culture may be beneficial in the production of recombinant protein and in maintenance of viability. The effects on cell cycle, apoptosis and nucleotide pools were studied in cultures initiated at 37°C and temperature shifted to 30 °C after 48 hours. In control cultures maintained at 37 °C, viable cells continued to proliferate until the termination of the culture, however, temperature reduction caused a rapid decrease in the percent of cells in S phase and accumulation o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
31
0

Year Published

1998
1998
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 165 publications
(33 citation statements)
references
References 28 publications
1
31
0
Order By: Relevance
“…Actively metabolizing cells maintain their growth arrest through inhibiting growth mechanisms. In addition to an increase in productivity induced by growth arrest, cultivation of cells under mild hypothermic conditions offers other relevant advantages: extended culture times (lower cell populations reduce overall nutrient uptake and waste production) [24], decreased O 2 demand [25], reduced intermolecular product aggregation [26], increased sensitivity to pH changes [27,28], and a decreased sensitivity to pro-apoptotic agents [29,30]. Protein sialylation [24], acidic glycoforms [31], and antennary structures [31] are relevant quality parameters that are improved in cells cultured under hypothermic conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Actively metabolizing cells maintain their growth arrest through inhibiting growth mechanisms. In addition to an increase in productivity induced by growth arrest, cultivation of cells under mild hypothermic conditions offers other relevant advantages: extended culture times (lower cell populations reduce overall nutrient uptake and waste production) [24], decreased O 2 demand [25], reduced intermolecular product aggregation [26], increased sensitivity to pH changes [27,28], and a decreased sensitivity to pro-apoptotic agents [29,30]. Protein sialylation [24], acidic glycoforms [31], and antennary structures [31] are relevant quality parameters that are improved in cells cultured under hypothermic conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, reduced culture temperature influences q p in a different fashion. It has been suggested that lowering culture temperature causes a shift in the proportion of cells from S to G1, which is partially responsible for increased q p [28,32]. It is well known that cells at G1 phase do not need to devote cellular resources to biomass production, thus subsequently can be employed for recombinant protein synthesis.…”
Section: Discussionmentioning
confidence: 99%
“…The suspension and the Cytodex 3 culture remained viable for a significantly longer period in the biphasic cultures than in the single-temperature cultures, leading to higher integrated cell densities. Moore and coworkers reported that low temperature culture leads to growth arrest in the G 0 /G 1 phase of the cell cycle and delays the onset of apoptosis (Moore et al 1997). Slikker and co-workers reported that hypothermia enhanced expression of the antiapoptosis protein, bcl-2, and protected against oxidative stress-induced cell death in CHO cells by increasing the activity of anti-oxidant enzyme, glutathione peroxidase (GSH-Px) (Slikker et al 2001).…”
Section: Discussionmentioning
confidence: 99%
“…The benefits of mild hypothermia include improved cell viability, reduced cell lysis from dead cells, reduced nutrient consumption rates, and often, improved productivity (Yoon et al 2003;Trummer et al 2006a). Despite the potential usefulness of mild hypothermia, there are significant limitations including G 0 /G 1 arrest (Moore et al 1997) and suppression of the cell growth, leading to low volumetric productivity. Biphasic culture, in which cells are cultivated at 37°C until they reach the maximum viable cell density, followed by a reduction in temperature to prolong cell longevity, presents a possible strategy to alleviate the disadvantages of hypothermia.…”
Section: Introductionmentioning
confidence: 99%